The Development of the Jurisprudential Opinion Consideration of the Modalities to Prove the Crescents: A Historical Jurisprudential Study in Shafi’i Books - Assuliman, Al-Motasem I A; Alqudah, Hazem Y M (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: The study aims to trace the development of jurisprudence opinion for the means of proving the emergence of the crescent in an endeavor to prove its effectiveness and dynamism. Methods: To achieve this, jurisprudential sources in the Shafi’i school were extrapolated by tracing the books of those who worked in the field in its early and late stages. Their statements were closely scrutinized and analyzed to reveal the nature of the means and tools used in their times, and how those scholars received them from a jurisprudential perspective. Results: The calculation presented sufficient results to know the birth of the crescent, but it was not accepted, and others to determine the possibility of sighting, and there was a dispute about it. As for astrology, it did not obtain what the calculation had. This was discussed in the first stage, and the dispute remained as it is. The research developed, and scholars studied the inconsistency of definitive computation with the testimony of vision, the issue of iron-sighted vision, and vision with a mirror and crystal, which paved the way for the research of the telescope. Conclusions: Jurists accumulatively investigated the modalities of astronomical and astrological calculations. They ended up depending on eyesight, the mirror, the binoculars, and the telescope. The study also recommended that the calculations evolved from the presumptive or conjectural results to the definitive or absolute.